2018
DOI: 10.1038/s41598-018-19794-0
|View full text |Cite
|
Sign up to set email alerts
|

New functions of Semaphorin 3E and its receptor PlexinD1 during developing and adult hippocampal formation

Abstract: The development and maturation of cortical circuits relies on the coordinated actions of long and short range axonal guidance cues. In this regard, the class 3 semaphorins and their receptors have been seen to be involved in the development and maturation of the hippocampal connections. However, although the role of most of their family members have been described, very few data about the participation of Semaphorin 3E (Sema3E) and its receptor PlexinD1 during the development and maturation of the entorhino-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…According to the literature, axons are forced to move away due to the expression of Sema3A, Sema3E, and Sema3F from the entorhinal cortex and pyramidal and granular layers to reach their proper targets in SLM and OML. Moreover, it has been suggested that low semaphorin expression may form an “axonal corridor” in the subicular region, allowing entorhinal axons to cross this region and reach the hippocampus [85]. However, from the research with Sema3A, Sema3E, and PlexinD1-deficient animals, we may conclude that these molecules are not solely responsible for the proper establishment of the connections.…”
Section: Semaphorins Their Receptors and Hippocampal Developmentmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the literature, axons are forced to move away due to the expression of Sema3A, Sema3E, and Sema3F from the entorhinal cortex and pyramidal and granular layers to reach their proper targets in SLM and OML. Moreover, it has been suggested that low semaphorin expression may form an “axonal corridor” in the subicular region, allowing entorhinal axons to cross this region and reach the hippocampus [85]. However, from the research with Sema3A, Sema3E, and PlexinD1-deficient animals, we may conclude that these molecules are not solely responsible for the proper establishment of the connections.…”
Section: Semaphorins Their Receptors and Hippocampal Developmentmentioning
confidence: 94%
“…For the establishment of the main afferent connection, the entorhino-hippocampal pathway (EH), Sema3A, Sema3E, and Sema3F have been implicated [30,83,84,85]. A highly accurate analysis of the mRNA expression of these semaphorins and their receptors has recently appeared in Mata et al, in which it was determined how these molecules undergo fine spatiotemporal regulation in embryonary/perinatal stages [85]. In mouse development, axons from layers II and III of the entorhinal cortex reach the hippocampal white matter and fimbria at E15 and start to invade the hippocampus at E16–E17, reaching the SLM.…”
Section: Semaphorins Their Receptors and Hippocampal Developmentmentioning
confidence: 99%
“…As Sema4A expression is also elevated in other CD4 + T cell-mediated diseases including, asthma, RA and MS [11,12,19,24], it is tempting to speculate that Sema4A-PlexinD1 signaling is involved in the dysregulation of Th cell homeostasis observed in these diseases and targeting this axis might be a beneficial therapeutic approach. As binding of PlexinD1 to its different ligands is not only involved in T cell differentiation, but also plays a key role in vascular, cardiac, skeletal and neuronal development and homeostasis [35][36][37][38][39][40], we consider that neutralizing Sema4A might be a better therapeutic option than blocking PlexinD1. A limitation of our study is that we could not test this possibility, due to the lack of commercially available anti-Sema4A neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidate interactors might be relevant to the functions of Rnd2 in adult-born DGNs. For example, semaphorin receptors, known as Plexins, have been implicated in AHN (Duan et al, 2014;Jongbloets et al, 2017;Mata et al, 2018;Zhao et al, 2018) and have been shown to be bound and regulated by Rnd2 in neurons and other cell types (Azzarelli et al, 2014;McColl et al, 2016;Uesugi et al, 2009). Nevertheless, whether Plexins mediate some aspects of Rnd2 action in adult newborn neurons remains unknown.…”
Section: Rnd2 Has Unique Functions In the Development Of Adult-born Dgnsmentioning
confidence: 99%